Patient education, risk communication and informed choice - Andermann, A; Andermann, Anne Adina Judith (2000)
﻿ This thesis describes research carried out to explore the needs, expectations and experiences of the increasing number of women with a family history of breast cancer who present to primary care. This work was intended to inform clinical practice and policy, and to directly address women's needs where possible. Although a great deal of research has looked at the experiences of women with a family history of breast cancer in a specialist setting, when this work began, no research had yet been published on women's needs in primary care. This is particularly important, as general practitioners (GPs) are the first port of call, and often the main source of information, advice and support. A qualitative interview study was used for the preliminary work exploring women's subjective experiences of consulting primary care about a family history of breast cancer and understanding their primary care consultation needs (Chapter 2). This work was further elaborated upon using a prospective descriptive study to quantify the extent to which women shared the same views or experiences, and therefore, would benefit from certain changes in health care provision (Chapter 3). The qualitative and quantitative research showed that women's main primary care consultation needs were to discuss their risks of breast cancer with their GP and to receive verbal as well as take-home information. When this work was being carried out, no patient information was available suitable for a general population of women with breast cancer in the family who present to primary care. For this reason, a leaflet was developed based on women's information needs and the best available evidence (Chapter 4). The leaflet entitled Breast and/or Ovarian Cancer in the Family: Learning More about Your Risks and Options was evaluated with almost 200 women to ensure that it met their needs (Chapter 5). Over 90% of women were glad to have received the leaflet and felt that it provided the information they wanted to know. The implications of the work described in this thesis are that GPs could greatly assist their patients by acknowledging family history concerns as a legitimate reason for presenting to primary care, by providing verbal and take-home information and by inviting patients to return for future discussions if needed. Nationally accepted management guidelines for breast cancer family history and accompanying educational materials for use in primary care will also be instrumental in meeting patient needs and promoting informed choice in this new and difficult area of medicine.